Describing implementation outcomes for a virtual community of practice: The ECHO Ontario Mental Health experience - Eva Serhal; Cheryl Pereira; Rosaria Armata; Jenny Hardy; Sanjeev Sockalingam; Allison Crawford (BMC, 2022)
Abstract Background Project ECHO is a virtual education model aimed at building capacity among healthcare providers to support optimal management for a range of health conditions. The expansion of the ECHO model, further amplified by the pandemic, has demonstrated an increased need to evaluate implementation success to ensure that interventions are implemented as planned. This study describes how Proctor et al.'s implementation outcomes (acceptability, adoption, appropriateness, costs, feasibility, fidelity, penetration, and sustainability) were adapted and used to assess the implementation of ECHO Ontario Mental Health (ECHO-ONMH), a mental health-focused capacity-building programme. Methods Using Proctor et al.'s implementation outcomes, the authors developed an implementation outcomes framework for ECHO-ONMH more generally. Using this, outcome measures and success thresholds were identified for each outcome for the ECHO-ONMH context, and then applied to evaluate the implementation of ECHO-ONMH using data from the first 4 years of the programme. Results An ECHO-ONMH implementation outcomes framework was developed using Proctor's implementation outcomes. ECHO-ONMH adapted implementation outcomes suggest that ECHO-ONMH was implemented successfully in all domains except for penetration, which only had participation from 13/14 regions. Acceptability, appropriateness and adoption success thresholds were surpassed for all 4 years, showing strong signs of sustainability. The programme was deemed feasible all 4 years and was found to be more cost-effective. ECHO-ONMH also showed high rates of fidelity to the ECHO model, and high rates of penetration. Conclusions This is the first study to use Proctor et al.'s implementation outcomes to describe implementation success for a virtual capacity-building model. The proposed ECHO implementation outcomes framework provides a base for similar interventions to evaluate implementation success, which is an important precursor to understanding learning, service or health outcomes related to the model. Additionally, these findings can act as a benchmark for other international ECHOs and educational programmes.